Mentoring in a medical faculty: a chance for organisational learning. (2018) - Petersen, Renate; Grümmer, Ruth; Jendrossek, Verena; Sauerwein, Wolfgang; Schara, Ulrike
The use of mentoring in academia as a strategy to support individual academic careers has a long tradition. It has been shown that the combination of mentoring as well as training sessions to acquire interdisciplinary key competences and networking activities is suitable for enhancing the individual's skills in various ways. In addition, it is evident that mentoring has a strong link to organisational learning as individual and institutional aims become connected and personal knowledge is transformed into collective knowledge. To date, the impacts of mentoring programs on the organisational development in universities have received little or no attention.